Neonatal nursing led research activity in the UK: a survey of current practice - Katie Gallagher; Julia Petty; Joanne Cooper; Neil Marlow (BMC, 2021)
Abstract Background Neonatal nurses are ideally placed in practice to undertake research enhancing the care of families. More information is required, however, around neonatal nursing led research to advance leadership in this area. The aim of this study was to determine neonatal nursing led research activity within the UK. Methods The study used a web-based survey design and neonatal nurses were eligible if they were working at or towards Masters or Doctoral level qualification in the UK. The survey was distributed to members of the Neonatal Nurses Association, UK Schools of Nursing and shared on social media pages of authors and professional organisations. Results were analysed using descriptive and frequency statistics and content analysis. Results Of the 56 respondents, 14% (n = 8) had a Doctoral level qualification and 43% (n = 24) of participants held a Masters qualification. Lack of time and funding knowledge was the largest barrier to research. Only 30% (n = 3) of participants had a research mentor and only 18% (n = 3) were from a neonatal nursing background. Conclusions There are limited numbers of neonatal nurses undertaking or leading nursing research in the UK. Further support is required to enhance clinical academic career trajectories to ensure research is a viable pathway for future generations of neonatal nurses.